Monitoring the performance and technique consolidation in youth football players - Esposito, Giovvani; Raiola, Gaetano (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The monitoring of the skills development datais especially important in youth soccer players. It should beimportant for the trainer in order to properly plan the training andachieve the highest possible adaptation of the individual athlete.Aim of Study. After an initial qualitative and quantitative testingphase, carried out in previous works, the aim of this study was tochoose adequate tests to evaluate the overall performance in theyoung players. Material and Methods. After an initial review ofthe literature, the research team chose three types of tests withthe technical components: T-drill Test (shooting), LoughboroughSoccer Passing Test (passage), Hoff Test (conduction). The firsttwo tests focus only on the agility component, while the third alsoevaluates resistance and agility. Tests were performed in 15 boysbetween 13 and 14 years of age practicing in an amateur footballschool. Results. The overall average time in the T-drill Test was15”53 without corrections for scored goals and 14”79 with suchcorrections. The average time achieved in the LSP Test was56”47 in the first attempt and 58”53 in the second attempt.Finally, in the Hoff Test, the boys covered an average distanceof 1512.8 m. Conclusions. By comparing the results obtainedfrom the sample with the reference data in the literature, it ispossible to examine the performance and the level of basic skills.These tests can also be used to identify talent in youth groups.
Keywords: agility; Loughborough Soccer Passing Test; T-drill Test; Hoff Test